Attenuated inflammatory response in infant mice with Staphylococcus epidermidis CNS catheter infection - Skar, Gwenn L.; Eaton, Kathryn; Beaver, Matt; White, Brian; Harris, Morgan; Snowden, Jessica N. (Frontiers in Bacteriology, 2023)
Children under one year of age are consistently found to be at the highest risk for shunt infection as a complication of hydrocephalus treatment, and repeated infections in the same patient are common. The mechanisms responsible for the increase in infant infection are not known. Our laboratory adapted our existing mouse model of Staphylococcus epidermidis central nervous system (CNS) catheter infection to characterize infection in infant mice as a foundation of on-going studies to determine the mechanisms of increased morbidity in infant shunt infections. The well-established model of S. epidermidis biofilm infection in the CNS was adapted to generate infection in 14-day old C57BL/6 mice. The catheter preparation was identical to the adult model, in which silicone catheters are pre-coated with a clinically derived biofilm-forming strain of S. epidermidis strain 1457) to introduce S. epidermidis into the brain. The catheters are stereotactically implanted into the lateral left ventricle. Bacterial titers as well as cytokine and chemokine levels were measured at days 1, 3, and 5 in mice implanted with sterile and S. epidermidis-coated catheters. Cultures demonstrated both catheter-associated and parenchymal infection through day 5 post-implantation. In contrast to prior adult models of CNS catheter infection, however, the catheter-associated bacterial burdens were less than or equal to parenchymal bacterial burdens. There was no significant difference between the chemokine and cytokine levels in the brain tissues of pups with sterile versus S. epidermidis infected catheters for any of the analytes tested. The infant model of S. epidermidis CNS catheter infection is characterized by both a greater degree of parenchymal spread of bacteria and the absence of the elevated pro-inflammatory cytokines previously observed in adult mice with this infection. The attenuated inflammatory response may contribute to the increased infection risk observed in this population.